Дядюшка в законе: [повесть] / Валерий Гусев - Гусев Валерий Борисович (Детский детектив, 2002)
Экземпляры: ф.13 (2002) / Инвентарный номер: 43933 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 96 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44